Peripheral Neuropathy Associated with Higher Mortality in Population with Chronic Kidney Disease: National Health and Nutrition Examination Surveys - Wei-Lan Li; Xiao-Yu Cai; Shu-Wang Ge; Gang Xu (Kidney Diseases, 2023)
Background: Peripheral neuropathy (PN), one of the commonest neurological complications of chronic kidney disease (CKD), was associated with physical limitation. Studies showed that a decrease in physical capability in patients with CKD is related with an increased risk of mortality. The objective of our research is directly exploring the relationship between PN and risk of mortality in patients with CKD. Method: 1836 participants with CKD and 6036 participants without CKD, which were classified by peripheral neuropathy based on monofilament examination in National Health and Nutrition Examination Survey (NHANES), were collected from the 1999 to 2004 National Health and Nutrition Examination Surveys. Multi-variable Cox proportional hazards models was conducted to assess the relationships of peripheral neuropathy and deaths in patients with CKD and non-CKD. Results: During 14 years of a median follow up from 1999 to 2015 and 2004 to 2015, 1072 (58.4%) and 1389 (23.0%) deaths were recorded in participants with CKD and without CKD, respectively. PN was related with increased all-cause mortality even after adjusting possible confounding factors in population with CKD (HR 1.34, 95% confidence interval [CI] 1.17-1.53) and without CKD (HR 1.27 95% CI 1.12-1.43). And the adjusted HRs (95% CI) for cardiovascular mortality of the people with CKD and without CKD who suffering from peripheral neuropathy were 1.42 (1.07, 1.90) and 1.23 (0.91, 1.67), respectively, versus those without peripheral neuropathy. Conclusion: PN was related with a higher risk of all-cause and cardiovascular death in people with CKD, which clinically suggests that the adverse prognostic impact of PN in the CKD population deserve attention and are an important target for intervention.